Use of powered air-purifying respirator(PAPR) as part of protective equipment against SARS-CoV-2-a narrative review and critical appraisal of evidence - Licina, Ana (Am J Infect Control, 2021)
BACKGROUND: The last 2 decades have seen an increasing frequency of zoonotic origin viral diseases leaping from animal to human hosts including Severe Acute Respiratory Syndrome Coronaviruses (SARS-CoV-2). Respiratory component of the infectious disease program against SARS-CoV-2 incorporates use of protective airborne respiratory equipment. METHODS: In this narrative review, we explore the features of Powered Air Purifying Respirators (PAPR) as well as logistical and evidence-based advantages and disadvantages. RESULTS: Simulation study findings support increased heat tolerance and wearer comfort with a PAPR, versus decreased communication ability, mobility, and dexterity. Although PAPRs have been recommended for high-risk procedures on suspected or confirmed COVID-19 patients, this recommendation remains controversial due to lack of evidence. Guidelines for appropriate use of PAPR during the current pandemic are sparse. International regulatory bodies do not mandate the use of PAPR for high-risk aerosol generating procedures in patients with SARS-CoV-2. Current reports of the choice of protective respiratory technology during the SARS-CoV-2 pandemic are disparate. Patterns of use appear to be related to geographical locations. DISCUSSION: Field observational studies do not indicate a difference in healthcare worker infection utilizing PAPR devices versus other compliant respiratory equipment in healthcare workers performing AGPs in patients with SARS-CoV-2. Whether a higher PAPR filtration factor translates to decreased infection rates of HCWs remains to be elucidated. Utilization of PAPR with high filtration efficiency may represent an example of “precautionary principle” wherein action taken to reduce risk is guided by logistical advantages of PAPR system.